2020
DOI: 10.1029/2019wr026667
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for the Release, Transport, and Retention of Per‐ and Polyfluoroalkyl Substances (PFAS) in the Vadose Zone

Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are emerging contaminants of critical concern. As surfactants, PFAS tend to accumulate at air‐water interfaces and may stay in the vadose zone for long times before contaminating groundwater. Yet not well understood, the extent of retention in the vadose zone has critical implications for risk management and remediation strategies. We present the first mathematical model that accounts for surfactant‐induced flow and solid‐phase and air‐water interfacial adsorption. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
139
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 74 publications
9
139
2
Order By: Relevance
“…The numerical simulations of PFAS leaching in the vadose zone reported by Guo et al (2020) are generally consistent with soil PFAS concentration profiles measured at contaminated sites.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…The numerical simulations of PFAS leaching in the vadose zone reported by Guo et al (2020) are generally consistent with soil PFAS concentration profiles measured at contaminated sites.…”
Section: Introductionsupporting
confidence: 76%
“…Numerical simulations of PFOS (Perfluorooctanesulfonic acid, C8HF17O3S) released at a model aqueous film-forming foam (AFFF)-impacted fire training area (FTA) site and the subsequent transport and retention in the vadose zone demonstrated that PFOS can be strongly retained in the vadose zone even under highly transient variably saturated flow driven by timedependent rainfall infiltration. Shortly after, a model similar to that of Guo et al (2020) was also independently reported by Silva et al (2020aSilva et al ( & 2020b, where example simulations were presented in both 1D and 2D domains.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…It is noted that this generic DAF was developed as a conservative approach to estimating groundwater concentrations associated with leaching from vadose zone soils based on a simple mass balance approach that compares source mass loading to groundwater flow and mixing with depth. Clearly, the SPLP is conservative in that it represents a saturated batch extraction whereby all air–water interfacial retention (see Brusseau et al, 2019; Guo et al, 2020) is eliminated with accelerated desorption as a result of aggressive agitation (e.g., Kalbe et al, 2008). Thus, SPLP results should not necessarily be expected to simulate actual porewater concentrations.…”
Section: Resultsmentioning
confidence: 99%